The peculiarities of the human mobility frame in the Romanian-Hungarian and Romanian-Ukrainean border area - Alexandru Ilies (Belgeo)
The present study illustrates the radiography of the situation of the Romanian-Hungarian and Romanian-Ukrainian cross-border areas reflected through the angle of cross-border dynamics, particularly during the post-communist period. The legislative and political context has changed perpetually and has had a profound impact on the free circulation of people. In the conditions in which Hungary is in the first wave of integration, Romania in the second and the Ukraine is only a partner and member of the CSI (Community of the Independent States), social-economic life in the contiguous areas of the three states becomes complex for the present situation but nevertheless optimistic as regards the future of the political European ensemble. Among the elements that diminish or enhance the permeability of the frontier, we mention here: the necessity of a visa and other formalities regarding access to the territory of another state, the number of border crossing points, the motivations that determine the dimension and the dominant direction of human flows.